Prevalência de insegurança alimentar em famílias de Pelotas, RS e estado nutricional das pessoas que vivem em insegurança alimentar - Santos, Janaína Vieira dos (2008)
A population-based cross-sectional study was conducted in Pelotas, Southern Brazil, with the objective of determining the prevalence of food insecurity in according to the other socioeconomic variables. Another aim of the study was to describe nutritional status of the family members who living in condition of food insecurity. The sample included 1,450 households of the urban area from Pelotas. In each household, six questions applied by interviewer were asked to the responsible by preparing meals and a score was constructed with the answers. If the household was classified as insecure, all members were weighed and measured in according to the standardized technical. Underweight, overweight and obesity were defined through different cut-offs points of body mass indices for children, adolescents and adults. The prevalence of food insecurity for the all families was of 11% (95%CI 9 to 13%). It was higher among families whose head of family was women (16%). Socioeconomic variables such as family income, economic level and schooling were inversely associated with food insecurity. The relationship between food insecurity and crowding was positive. For all family members living in food insecurity, overweight and obesity were more frequent than underweight. The differences were higher among adult than the others. Twenty percent of children living in food insecurity presented deficit in height. The authors conclude that may there is both quantitative and qualitative components of food insecurity.